Genesis of magnesite deposits in the view of isotope geochemistry - SCHROLL, ERICH (Boletim Paranaense de Geociências, 2002)
Isotopic data, i.e. δ 13 C and δ 18 O including 86 Sr/87 Sr, are the fundamental data to characterize geochemically magnesite mineralizations. Other geochemical data, e.g. chemical data, REE and fluid chemistry, are supplementary characteristics for genetic models. The geological setting and the origin of magnesium are relevant to classify magnesites genetically. The δ 13 C - δ 18 O - diagrams of magnesite and siderite are significantly different. Stratabound magnesite is dominated by the isotopic signature of carbonate sediments, while siderites from occurrences with economic importance preferably show light carbon isotope like the ultramafic-hosted vein type mineralization. The δ 18 O original values of sparry magnesites are strongly influenced by burial and grade of metasomatism. Thus, the origin of sparry magnesite hosted by metasediments is to be considered as a sedimentary enrichment influenced by diagenetic and metamorphic processes. An approach to the best genetic model of each magnesite deposit needs the synopsis of all geological facts and geochemical data.